Early experiences of the Your COVID Recovery® digital programme for individuals with long COVID. Issue 1 (28th September 2022) - Lloyd-Evans, Phoebe H I; Baldwin, Molly M; Daynes, Enya; Hong, Annabel; Mills, George; Goddard, Amye C N; Chaplin, Emma; Gardiner, Nikki; Singh, Sally J
Abstract : Objectives: To describe the early data from the Your COVID Recovery ® digital programme and to explore the data collected from two embedded outcome measures. Design: Observational. Setting: Primary and secondary care (England—Online). Participants: 110 individuals completed the programme (68.1% female, 88.1% White British, age: 46.3 (10.8) years, weight: 86.5 (21.1) kg, height: 169.3 (10.0) cm). 47.2% of patients reported comorbidities. Intervention: Following an assessment by a healthcare professional, individuals with long COVID were offered access to the Your COVID Recovery ® digital programme. The programme comprises of four stages for the participants to progress through. Participants are encouraged to record severity of their symptoms and amount of activity they are doing on a symptom and an activity tracker. Resources and interactive material on managing symptoms of long COVID are available throughout each stage. Primary outcome measures: Questionnaire (EuroQ0l 5-Dimension 5-Level (EQ-5D-5L) and the chronic obstructive pulmonary disease assessment test (CAT)) data were extracted from the site from 11 March 2021 until 9 November 2021. Results: Participants were on the programme for 8.6 (4.3) weeks. There was a statistically significant increase in EQ-5D-5L visual analogue scale (VAS) score (pre=48.8 (19.5); post=59.9 (22.1); p<0.01). The EQ-5D-5L Index Value preintervention to postintervention did improve but not significantly (pre=0.5 (0.3); post=0.6 (0.3); p=0.09). CAT total score improved significantly preintervention to postintervention (pre=19.8 (7.2); post=15.6 (7.6); p<0.01). All CAT item scores significantly improved preintervention to postintervention (p<0.005), except the phlegm item score (p=0.168). Discussion: This early data describes the impact of the Your COVID Recovery ® digital programme on the first cohort of patients to complete the digital recovery programme. The outcome data are promising and should encourage uptake.